2016
DOI: 10.1021/acs.orglett.6b03019
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 1,2,4-Triazole Derivatives via Cyclocondensation of Alkylidene Dihydropyridines and Aryldiazonium Salts

Abstract: Alkylidene dihydropyridines (anhydrobases) prepared via dearomatization of N-acylated 4-(aminomethyl)pyridines participate in [3 + 2] cyclocondensation reactions with aryldiazonium cations to afford substituted 1,2,4-triazolium salts or neutral 1,2,4-triazoles in high isolated yield. The reaction proceeds in the presence of a variety of N-acyl groups and aryl-susbtituted diazonium salts and offers a general route to pyridyl-substituted 1,2,4-triazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Clearly, both indazole and 1,2,4-triazole are valuable heterocyclic structures. Their derivatives are a versatile class of compounds found in numerous natural products and biologically active compounds.…”
supporting
confidence: 62%
“…Clearly, both indazole and 1,2,4-triazole are valuable heterocyclic structures. Their derivatives are a versatile class of compounds found in numerous natural products and biologically active compounds.…”
supporting
confidence: 62%
“…In 2016, the Pigge group developed a novel and efficient synthetic approach to pyridyl-substituted 1,2,4-triazoles and triazolium salts via cyclocondensation of alkylidene dihydropyridines and aryldiazonium salts (Scheme 26). [38] The alkylidene dihydropyridines (anhydrobases) which were generated in situ from pyridines and ClCO 2 Et in THF participated in [3 + 2] cyclocondensation reactions with aryldiazonium cations to afford functionalized 1,2,4-triazolium salts and 1,2,4-triazoles in moderate to good yields. High atom economy, readily available starting materials, good functional group tolerance, and mild reaction conditions render this protocol attractive for the construction of 1,2,4-triazole containing bioactive molecules.…”
Section: Synthesis Of 124-triazoles and Their Derivativesmentioning
confidence: 99%
“…Finally, we found that the exocyclic alkenes in pyridine anhydrobases (III) are amenable to reactions before rearomatization to form other valuable pyridine derivatives (Scheme 2). [14] After subjecting 3-phenylpyridine N-triazinyl salt to the dearomatization-olefination sequence, we used the crude material containing III-3-Ph without purification.…”
Section: Methodsmentioning
confidence: 99%